Problematika Manajemen Sarana dan Prasarana dalam Meningkatkan Mutu Pembelajaran - Murniyanto; Arista, Helsi; Sartika, Devi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Good management of facilities and infrastructure is an effort to improve the quality of learning through planning, organizing, managing and evaluating to support teachers in planning learning, the learning process and evaluating student learning outcomes to achieve quality learning goals. This research aims to describe the problems of managing facilities and infrastructure in improving the quality of learning. This research methodology uses a descriptive qualitative approach, the informants are the head of the Madrasah Nurul Fatah Tsanawiyah and the Teacher Madrasah Tsanawiyah Nurul Fatah. Data collection techniques interviews, observation and documentation. Test the validity of technical triangulation data. The research results show that adequate facilities and infrastructure need to be improved for the smooth running of education and improvement of the quality of learning. Thus, it can be concluded that at Madrasah Tsanawiyah Nurul Fatah there is still a need for good management of facilities and infrastructure to minimize the ineffectiveness of both intra curricular and extracurricular learning activities. To improve the quality of learning, it is very necessary to carry out good management of facilities and infrastructure because this is the key to success in education work.